Corporate Social Resposonsibility w kontekście imperatywu kategorycznego Kanta - Tapek, Krzysztof (Annales. Etyka w Życiu Gospodarczym, 2016)
Immanuel Kant’s philosophy, especially his categorical imperative, is one of several ethical theories mainly used to morally legitimize actions, referred to as Corporate Social Responsibility. The aim of the current article is to evaluate if Kant’s philosophy can be used as the ethical foundation for Corporate Social Responsibility as well as to present its advantages and disadvantages in a theoretical and practical approach.